2017
DOI: 10.1021/acs.jchemed.7b00158
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Octadecyltrichlorosilane Nanopatterns Using Particle Lithography: An Atomic Force Microscopy Laboratory

Abstract: Experiments are described that involve undergraduates learning concepts of nanoscience and chemistry. Students prepare nanopatterns of organosilane films using protocols of particle lithography. A few basic techniques are needed to prepare samples, such as centrifuging, mixing, heating, and drying. Students obtain hands-on skills with nanoscale imaging using an atomic force microscope (AFM) when they learn to characterize samples. Designed surfaces are made using a surface mask of latex or silica spheres to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…A solution of nanospheres was prepared by diluting the stock nanosphere solution 1:1 with water to generate a monolayer of nanospheres on the Si substrate. Surfactant from the nanosphere solution was washed off by vortexing and centrifugation to promote intersphere interactions as previously reported. , The spheres pack well on the surface in a repeating hexagonal arrangement, as shown in Figure b and d, due to intersphere interactions and capillary forces. During formation of the OTS SAM (Figure c and d), the contact of the spheres with the substrate effectively mask self-assembly of OTS on those areas, creating nanopores (Figure e and f) at the sphere contact locations with diameters determined by the contact area and spacing determined by the nanosphere diameter.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A solution of nanospheres was prepared by diluting the stock nanosphere solution 1:1 with water to generate a monolayer of nanospheres on the Si substrate. Surfactant from the nanosphere solution was washed off by vortexing and centrifugation to promote intersphere interactions as previously reported. , The spheres pack well on the surface in a repeating hexagonal arrangement, as shown in Figure b and d, due to intersphere interactions and capillary forces. During formation of the OTS SAM (Figure c and d), the contact of the spheres with the substrate effectively mask self-assembly of OTS on those areas, creating nanopores (Figure e and f) at the sphere contact locations with diameters determined by the contact area and spacing determined by the nanosphere diameter.…”
Section: Resultsmentioning
confidence: 93%
“…Silane-based monolayer formation is a well-studied process that involves the hydrolysis and subsequent condensation with surface hydroxyl groups to form a uniform, monolayer thick coating on the silicon surface with OTS molecules utilizing their longer alkyl chains to produce particularly well-packed SAMs films. , The residual water on the native oxide of silicon plays a critical role in the monolayer formation process as it is required for the hydrolysis reactions . Therefore, the effect of relative humidity on the fabrication process was investigated to optimize the monolayer formation conditions. , Garno et al previously demonstrated that the relative humidity at which the samples are dried prior to monolayer formation effects the quality, packing, and thickness of the monolayer formed on the SiO 2 surface . Our results, shown in Figure S1, demonstrate the importance of the relative humidity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atomic force microscopy has been a useful tool in chemistry and materials science due to its exquisitely high spatial resolution that has been used to visualize materials, molecules, and atoms. , However, using an atomic force microscope (AFM) in the laboratory curriculum is typically restricted to upper-division undergraduate or higher-level courses. At the lower-division undergraduate level, AFM use is uncommon and generally restricted to laboratories with fewer than 10 students or to use of the AFM as a demonstration during class . To understand and take full advantage of its technical capabilities, an understanding of an AFM’s operating principles is necessary, and in our view, should start at the first-year undergraduate level.…”
Section: Introductionmentioning
confidence: 99%